Platon und die Zeit - Männlein-Robert, Irmgard; Corcilius, Klaus (Mohr Siebeck, 2024)
Plato and Time.
PublicationDate: 20250107
Keywords: Kosmologie -- Schicksal -- Ewigkeit -- Ontologie -- Religionsphilosophie -- Antike -- Antike Philosophie -- Allgemeines -- Ethik -- Anthropologie -- Ästhetik -- Erkenntnistheorie -- Kulturphilosophie -- Metaphysik -- Ethics -- Array